EFEKTIVITAS PEMBERIAN KOMBINASI PRODUK HERBAL DAN ANTIBIOTIK TERHADAP INFEKSI SALMONELLA TYPHIMURIUM PADA MENCIT BALB/C - Yanuarita Tursinawati; Edi Dharmana (Universitas Muhammadiyah Semarang, 2015)
Background : Medicinal herbs contained in Tolak Angin Cair (TAC), a Standardized Herbal Medicine has immunostimulant and antimicrobial effect. This research is aimed to examine the effectiviness of TAC, a herbal product and chloramphenicol,an antibiotic combination against S.typhimurium which is represented by bacterial colony count in Balb/c mice’s liver. Methods : The experimental study with post test only control group design used 20 Balb/c female mice,randomly divided into 4 groups:control (aquades group), P1 (chloramphenicol group), P2 (Tolak Angin Cair group), and P3 (combination of Tolak Angin Cair-chloramphenicol group). All groups were infected by 105 CFU of S. thypimurium at 1st day and given the treatment until 5th day. Data were analyzed by Mann-Whitney test (CI 95% and significance value p<0,05). Results: The number of bacterial colony was P2 (50.927.000+72.446.458,2 cfu/gram), K (10.583.000+14.623.899,8 cfu/gram),P1 and P3 (0 cfu/gram). There was significantly decreasing of bacterial colony between P3 to K (p=0,005). There was no significantly difference between P1 and P3 (p=1). Conclusions: Herbal product and antibiotic combination can decrease the bacterial colony in Balb/c mice’s liver which infected by S. thypimurium. These combination is as effective as a single administration of chloramphenicol. Single administration of herbal product fail to eliminate bacteria.Keywords: herbal product, antibiotic, Tolak Angin Cair, chloramphenicol, Salmonella typhimurium